2024
DOI: 10.2334/josnusd.23-0166
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a highly-filled flowable composite for the repair of indirect composites

Özlem Kanar,
Simge Meşeli,
Bora Korkut
et al.

Abstract: Purpose: To compare the shear-bond-strength (SBS) of a highly-filledflowable composite (HFFC) and a paste-type composite for indirect composite repair and to evaluate the effect of different surface treatments (ST), concerning the composite repair protocol. Methods: Eighty-four 5 × 5 × 2 mm cylindrical specimens were prepared using Gradia Plus and SR Nexco indirect composite materials. The samples were thermocycled 5,000 times. According to the ST, the samples were divided into three groups (control, bur, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Icon resin infiltration has been recently introduced by developing a highly flowable resinous material that was proved to cause an immediate aesthetic masking of mild WSLs to match the adjacent sound enamel (Kanar et al 2024). It was reported that Icon resin infiltration could be applied without significant color change up to 6 months (Knösel et al 2019).…”
mentioning
confidence: 99%
“…Icon resin infiltration has been recently introduced by developing a highly flowable resinous material that was proved to cause an immediate aesthetic masking of mild WSLs to match the adjacent sound enamel (Kanar et al 2024). It was reported that Icon resin infiltration could be applied without significant color change up to 6 months (Knösel et al 2019).…”
mentioning
confidence: 99%